2022
DOI: 10.3389/fcvm.2022.976844
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a clinical predictive model for 1-year prognosis in coronary heart disease patients combine with acute heart failure

Abstract: BackgroundThe risk factors for acute heart failure (AHF) vary, reducing the accuracy and convenience of AHF prediction. The most common causes of AHF are coronary heart disease (CHD). A short-term clinical predictive model is needed to predict the outcome of AHF, which can help guide early therapeutic intervention. This study aimed to develop a clinical predictive model for 1-year prognosis in CHD patients combined with AHF.Materials and methodsA retrospective analysis was performed on data of 692 patients CHD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Some studies reported that demographic information (age), clinical manifestations (NYHA functional class, SBP, DBP, and MAP), pre‐existing conditions (diabetes mellitus and AF), medications (vasopressors), laboratory tests (NT‐proBNP, haemoglobin, sodium, albumin, creatinine, blood urea nitrogen, and eGFR), and 12‐lead resting ECG (RBBB) were significantly associated with OS 8,9,37–40 . However, in the other studies, there was no apparent association of demographic information (age), clinical manifestations (SBP and DBP), pre‐existing conditions (AF), medications, and laboratory tests (NT‐proBNP, haemoglobin, sodium, and creatinine) with long‐term survival 41–43 . To our knowledge, this study is the first risk stratification model to consider including VHD, CRT, and indicators of SPECT MPI (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies reported that demographic information (age), clinical manifestations (NYHA functional class, SBP, DBP, and MAP), pre‐existing conditions (diabetes mellitus and AF), medications (vasopressors), laboratory tests (NT‐proBNP, haemoglobin, sodium, albumin, creatinine, blood urea nitrogen, and eGFR), and 12‐lead resting ECG (RBBB) were significantly associated with OS 8,9,37–40 . However, in the other studies, there was no apparent association of demographic information (age), clinical manifestations (SBP and DBP), pre‐existing conditions (AF), medications, and laboratory tests (NT‐proBNP, haemoglobin, sodium, and creatinine) with long‐term survival 41–43 . To our knowledge, this study is the first risk stratification model to consider including VHD, CRT, and indicators of SPECT MPI (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…8,9,37-40 However, in the other studies, there was no apparent association of demographic information (age), clinical manifestations (SBP and DBP), pre-existing conditions (AF), medications, and laboratory tests (NT-proBNP, haemoglobin, sodium, and creatinine) with long-term survival. [41][42][43] To our knowledge, this study is the first risk stratification model to consider including VHD, CRT, and indicators of SPECT MPI (i.e. rest scar burden) to predict the prognosis of AHF.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Lp‐PLA 2 levels may reflect the degree of atherosclerotic plaque instability and the severity of coronary artery disease 13 . Huang et al reported a positive correlation between plasma Lp‐PLA 2 concentrations and major adverse cardiovascular events in patients experiencing acute myocardial infarction, which intimates a potential role for Lp‐PLA 2 in the pathogenesis and progression of myocardial infarction 14 . Nevertheless, the correlation between Lp‐PLA 2 and CVD in T2DM warrants further rigorous investigation.…”
Section: Introductionmentioning
confidence: 99%